Boundary Extension in Face Processing. (August 2017) - Blazhenkova, Olesya
Boundary extension is a common false memory error, in which people confidently remember seeing a wider angle view of the scene than was viewed. Previous research found that boundary extension is scene-specific and did not examine this phenomenon in nonscenes. The present research explored boundary extension in cropped face images. Participants completed either a short-term or a long-term condition of the task. During the encoding, they observed photographs of faces, cropped either in a forehead or in a chin area, and subsequently performed face recognition through a forced-choice selection. The recognition options represented different degrees of boundary extension and boundary restriction errors. Eye-tracking and performance data were collected. The results demonstrated boundary extension in both memory conditions. Furthermore, previous literature reported the asymmetry in amounts of expansion at different sides of an image. The present work provides the evidence of asymmetry in boundary extension. In the short-term condition, boundary extension errors were more pronounced for forehead, than for chin face areas. Finally, this research examined the relationships between the measures of boundary extension, imagery, and emotion. The results suggest that individual differences in emotional ability and object, but not spatial, imagery could be associated with boundary extension in face processing.